A vacuolar membrane protein Avt7p is involved in transport of amino acid and spore formation in Saccharomyces cerevisiae. Issue 2 (1st February 2015) - Tone, Junichi; Yamanaka, Atsushi; Manabe, Kunio; Murao, Nami; Kawano-Kawada, Miyuki; Sekito, Takayuki; Kakinuma, Yoshimi
Abstract: Active transport systems for various amino acids operate in the vacuolar membrane of Saccharomyces cerevisiae . The gene families for vacuolar amino acid transporters were identified by reverse genetics experiments. In the AVT transporter family, Avt1p works for active uptake of amino acid into vacuole, and Avt3p, Avt4p, and Avt6p for active extrusion of amino acid from vacuole to cytosol. Here, we found green fluorescent protein-tagged Avt7p, an unidentified member of the AVT family, localized to the vacuolar membrane of S. cerevisiae . Disruption of the AVT7 gene enhanced both vacuolar contents of several amino acids and uptake activities of glutamine and proline by vacuolar membrane vesicles. Efficiency of spore formation was impaired by the disruption of the AVT7 gene, suggesting the physiological importance of Avt7p-dependent efflux of amino acid from vacuoles under nutrient-poor condition. Graphical abstract: : Disruption or overexpression of AVT7 encoding a member of AVT transporter family affects net uptake of glutamine and proline by vacuolar membrane vesicles.